РЕГУЛЮВАЛЬНІ ХАРАКТЕРИСТИКИ АКТИВНОГО ЧОТИРИКВАДРАНТНОГО ПЕРЕТВОРЮВАЧА В РЕЖИМАХ ВИПРЯМЛЕННЯ І РЕКУПЕРАЦІЇ - Щербак , Я.В.; Плахтій , О.А.; Нерубацький , В.П. (Інститут електродинаміки НАН України, Київ, 2017)
High-speed train is supplied by alternating current (AC) power and bases on single-phase four quadrant (4Q) converter as one necessary part of the AC-DC-AC transform process. This paper introduce hysteresis control system of 4Q-converter and it’s regulating characteristics. Regulating characteristics are obtained on the basis of energy balance equation and describes dependence of output voltage and regulating coefficient of the hysteresis control system ξ in rectifier-mode and recuperation-mode. The nonlinear character of the control characteristic and its dependence on the load current is determined. It is concluded that for a steady process of rectification and recovery, the automatic control system must contain a feedback channel of the load current. A 4QS-converter model was developed in the Matlab simulation environment where the theoretical positions of output voltage regulation and high power quality parameters in rectification and recovery modes were confirmed. References 10, figures 6.